2022
DOI: 10.1021/acsomega.2c04773
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Na0.4MnO2 Microrods for Room-Temperature Oxidation of Sulfurous Gases

Abstract: Phase pure Na0.4MnO2 microrods crystallized in the orthorhombic symmetry were fabricated for the wet oxidation of H2S and SO2 gases at room temperature. The material was found highly effective for the mineralization of low concentrations of acidic gases. The material was fully regenerable after soaking in a basic H2O2 solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…Even in previously reported work on SO 2 adsorption over Na 0.4 MnO 2 , we have observed sulphate as the sole S species. 25 Here, the S 2p peak is fitted with a single 2p 3/2 –2p 1/2 doublet with 2p 3/2 peak at 168.8 eV for sulphate species, which agrees with the literature (Fig. 10a).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Even in previously reported work on SO 2 adsorption over Na 0.4 MnO 2 , we have observed sulphate as the sole S species. 25 Here, the S 2p peak is fitted with a single 2p 3/2 –2p 1/2 doublet with 2p 3/2 peak at 168.8 eV for sulphate species, which agrees with the literature (Fig. 10a).…”
Section: Resultssupporting
confidence: 90%
“…28 Previously, H 2 S oxidation to sulphur and sulphate has been reported for Na 0.4 MnO 2 , where all three species were confirmed after H 2 S adsorption. 25 Thus, dissociative H 2 S adsorption over the Mn-sites of Li 2 MnO 3 is accompanied by the transfer of electrons to the oxide surface, which is confirmed by a decrease in the Mn 4+ / (Mn 3+ + Mn 2+ ) ratio from 1.08 (for Li 2 MnO 3 ) to 0.81 (for Li 2 M-nO 3 _H 2 S). This ratio decrement further confirmed that H 2 S chemisorption is accompanied by the transfer of electrons from H 2 S molecules over the Li 2 MnO 3 surface (Fig.…”
Section: Njcmentioning
confidence: 80%
See 1 more Smart Citation
“…Ene_R, after SO 2 or NO 2 adsorption, was regenerated by soaking in a binary NaOH-H 2 O 2 solution. 14 The PXRD analysis showed an insignificant change in the material composition after the regeneration process (Figure S8). For the three regeneration cycles, Ene_R exhibited an average SO 2 and NO 2 adsorption capacity of 30.2 and 13.8 mg g −1 , respectively (Figures 3c, 3d), showing an excellent potential of the battery waste material as a regenerable adsorbent for toxic gas removal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequently, these extracted materials were evaluated in column configurations to determine their SO 2 and NO 2 gas adsorption capacities. Moreover, the material’s reusability performance was evaluated after regenerating the spent adsorbent with the NaOH-H 2 O 2 solution . Additionally, spectroscopic analysis and theoretical calculations were conducted to understand the underlying adsorption mechanisms.…”
Section: Introductionmentioning
confidence: 99%